O espaço do corpo - Maria Eduarda Ramos Cardoso (2016)
The present dissertation intends to reflect about the Body as a fundamental point of the current architectural thinking and as a key element for the development and recognition of a cross-cutting strategy to anyone who thinks about Architecture. My body, your body, our bodies. We exist because we have a body. We live in a world of bodies. We are the complex human body, we stand us by our physical and mental duality, by the interior and exterior relational link. The Architecture exists because we, body, create it, because we think about it, because we build it, because we use it, because we challenge it and because we are totally dependent on it. The whole process of architectural existence involves an infinite network of bodies that aspire to find an adequate answer to a specific problem. We are bodies of Architecture that are related to each other, relating time and space through body movements and that explore the true meaning and limits of the places through experience. We percept, feel, grasp, memorize, internalize, measure, draw in and the space, we are confronted and encountered constantly with Architecture. In an interlaced journey between Architecture and Dance we intend to relate concepts analogous to the two areas of study. Through the link between practices of choreographic creation and participation we will explore body as the core of thought and experience in space. Throughout the investigation we will seek to defend an architectural logic inseparable of knowledge of architect body, able to absorb and understand the multiple bodies and variables surrounding it.